Efektivitas Jogja Smart Service dalam Pelayanan Kependudukan ditengah Pandemi Covid-19 - Faizatur Rochmah; Fairuz Arta Abhipraya; Sakir Sakir (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2021)
In the midst of the Covid-19 pandemic, the Yogyakarta City Population and Civil Registration Service implements social distancing or reduces face to face in population administration services. People only need to access the Jogja Smart Service application to take care of population administration. Jogja Smart Service is one of the implementations of e-government in the administration of Yogyakarta City government. The purpose of this research is to determine whether or not the Jogja Smart Service (JSS) application is effective in the population services of the people of Yogyakarta City amid the Covid-19 pandemic. This research uses descriptive qualitative method. Data collection techniques were carried out by means of interviews and literature studies. The data analysis used is descriptive analysis, namely describing and analyzing more deeply related to the findings of research using existing theoretical foundations. To determine whether or not Jogja Smart Service is effective in population services in the midst of the Covid-19 pandemic, this study uses five indicators, namely tangiable, reliability, responsiveness, assurance and empathy. The results of this study indicate that the Jogja Smart Service application has succeeded in serving the population administration of the people of Yogyakarta City in the midst of the Covid-19 pandemic effectively and efficiently even though in its implementation there are still obstacles.